LAMANG DAN TRADISI MALAMANG PADA MASYARAKAT MINANGKABAU - NFN Refisrul (Balai Pelestarian Nilai Budaya Sumatera Barat, 2018)
Lamang is a typical food of Minangkabau society made from puluik rice with container from gutters(bamboo). Making lamang become the tradition of Minangkabau society since ancient times andcommonly referred to as nightang tradition. Lamang and night traditions are interesting and need toknow more in deep relationship in Minangkabau society life. This study uses a qualitative approach todata and information that is complete and in-depth. Nighttime tradition is the expression of Minangkabausociety towards the form of biological fulfillment and their fellow social relation, both within the widercircle of relatives and society. The existence of the night tradition is stronger the bonds of kinship,solidarity and symbols between peers. That is, the food lamang (lemang), as one of traditional food,and night traditions related to the culture of its people Minangkabau culture.